THE ECONOMIC EFFICIENCY OF DIGITALIZATION IN TRANSPORTATION: A SYSTEMATIC REVIEW OF APPLICATIONS AND IMPACTS - Shahzodahon Ghulomjonova, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Digitalization in transportation, encompassing technologies such as AI,  IoT,  blockchain,  and  big  data  analytics,  has  emerged  as  a  pivotal  driver  for enhancing  economic  efficiency  amid  global  challenges  like  cost  pressures,  supply chain  disruptions,  and  sustainability  demands.  This  study  conducts  a  systematic literature  review  (SLR)  following  PRISMA  guidelines  to  evaluate  the  economic impacts of digitalization in transport sectors, focusing on cost reductions, productivity gains, and sustainability synergies. Drawing from Scopus-indexed articles published between  2020  and  2025,  the  review  analyzes  15  key  studies.  Results  indicate  that digital technologies can yield up to 20-50% cost savings in logistics through optimized routing and predictive maintenance, while also reducing carbon emissions by 10-30% via  efficient  fleet  management.  However,  implementation  barriers,  including  high initial investments and regional disparities, moderate these benefits. The discussion highlights  policy  implications  for  fostering  digital  adoption  to  achieve  sustainable economic growth in transportation.